A single‐synapse resolution survey of PSD95‐positive synapses in twenty human brain regions. (25th June 2020) - Curran, Olimpia E.; Qiu, Zhen; Smith, Colin; Grant, Seth G.N.
Abstract: Mapping the molecular composition of individual excitatory synapses across the mouse brain reveals high synapse diversity with each brain region showing a distinct composition of synapse types. As a first step towards systematic mapping of synapse diversity across the human brain, we have labelled and imaged synapses expressing the excitatory synapse protein PSD95 in twenty human brain regions, including 13 neocortical, two subcortical, one hippocampal, one cerebellar and three brainstem regions, in four phenotypically normal individuals. We quantified the number, size and intensity of individual synaptic puncta and compared their regional distributions. We found that each region showed a distinct signature of synaptic puncta parameters. Comparison of brain regions showed that cortical and hippocampal structures are similar, and distinct from those of cerebellum and brainstem. Comparison of synapse parameters from human and mouse brain revealed conservation of parameters, hierarchical organization of brain regions and network architecture. This work illustrates the feasibility of generating a systematic single‐synapse resolution atlas of the human brain, a potentially significant resource in studies of brain health and disease. Abstract : Using single‐synapse resolution molecular imaging and sophisticated image analysis to uncover the distribution of the excitatory synapse protein PSD95 in the human brain reveals regional signatures in synapse parameters and conservation in hierarchical synaptome architecture with the mouse brain. This study constitutes a first key step towards a systematic human brain synaptome atlas.